Intraoral fluoride levels after use of conventional and high-fluoride dentifrices - Pessan, Juliano Pelim [UNESP]; Conceição, Juliana Mendonça da [UNESP]; Grizzo, Larissa Tercílio; Szekely, Melinda; Fazakas, Zita; Buzalaf, Marilia Afonso Rabelo (Springer, 2015)
This study aimed to evaluate saliva and plaque as indicators of intraoral fluoride (F) levels after the use of conventional and high-fluoride dentifrices.Subjects were randomly assigned to brush their teeth with conventional (1000 ppm F), high-fluoride (5000 ppm F), and placebo dentifrices (fluoride free) for 10 days, following a double-blind, crossover protocol. Saliva and plaque samples were collected on the morning of the 5(th) and 10th days, respectively at 1 and 12 h after brushing, and analyzed with an ion-selective electrode after HMDS-facilitated diffusion. Data were analyzed by two-way repeated measures ANOVA, Tukey's test and Spearman's correlation coefficient (p < 0.05).Plaque and salivary F levels were significantly increased after the use of conventional and high-fluoride dentifrices when compared to values obtained for placebo, except plaque 12 h after the use of conventional dentifrice. A positive and significant correlation was found between fluoride concentrations in plaque and saliva for both times of sample collection.Both indicators assessed were able to detect significant differences among treatments and between times after brushing. The use of a high-fluoride dentifrice is able to significantly increase intraoral fluoride levels throughout the day, being therefore a useful therapy for patients at high caries risk.A dentifrice with high fluoride concentration could be regarded as a useful therapy of F delivery for high caries-risk patients, since intraoral F levels were sustained throughout most of the day after using this formulation.
Keywords: Fluoride; Saliva; Plaque; Dentifrice; Dental biofilm